Membangun Toleransi Melalui Keberagaman Sosial Budaya Dalam Pendidikan Siswa - muhammad bustanul arifin; Muhammad Asvani PL (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This article examines the problems in schools as educational institutions that must be able to respect diversity to prevent ethnic conflict. Important things in multicultural education are awareness of the important values ​​of cultural diversity, educational reform movements, and educational processes. Various forms of gender disparities that occur in community life also occur in the world of education. Educational institutions play a major role in socializing and preserving the values ​​and perspectives that underlie the emergence of various gender inequalities in society ACCORDING to MPR Decree No. IV of 1999 concerning GBHN which regulates the position and role of women.